Effects of Nominal Maximum Aggregate Size on the Performance of Stone Matrix Asphalt - Hongying Liu (Highway College, Chang’An University, Xi’an 710064, China) (MDPI AG, 2018)
It is well known that the performance of hot mix asphalt (HMA) in service life is closely related to a proper aggregate gradation. A laboratory study was conducted to investigate the effects of nominal maximum aggregate size (NMAS) on the performance of stone matrix asphalt (SMA). The volumetric characteristics and performance properties obtained from wheel tracking tests, permeability test, beam bending test, contabro test are compared for SMA mixes with different NMAS. The results indicated that voids in mineral aggregate (VMA) and voids filled with asphalt (VFA) of SMA mixtures increased with a decrease of aggregate size in aggregate gradation. SMA30 had the lowest optimum asphalt content among all the mixtures. Increase of NMAS contributed to improvement of the rutting resistance of SMA mixtures. However, a decrease of NMAS showed better cracking and raveling resistance. Permeability rate of SMA was primarily affected by the air voids (AV) and break point sieve, but was also sensitive to aggregate gradation to some extent, with reduced NMAS corresponding to less permeability rate. Based on the test results, SMA5 and SMA13 are suggested to be used as a water-proof layer in bridge deck pavement, and SMA20 and SMA30 are suggested to be used as binder course in asphalt pavement, which needs to possess superior rutting resistance at high temperature.